Precise allele-specific genome editing by spatiotemporal control of CRISPR-Cas9 via pronuclear transplantation - Yanhe Li (Nature Portfolio, 2020)
Injecting Cas9 and gRNA into an animal zygote often produces mosaicism and random biallelic targeting. Here, the authors use pronuclear transfer to reduce mosaicism and selectively target parental alleles.